Reformulation of Regulatory Protection for Resident Doctors Against Bullying in Specialist Medical Education - Effendy, Meyland Citra Oktri Sienty; Fikri, Ahmad Ma’mun; Anwar (LifeSciFi, 2025)
The phenomenon of bullying against participants in the Medical Specialist Education Program within teaching hospital environments highlights structural inequalities and legal gaps in Indonesia’s advanced medical education system. This study aims to analyze legal issues concerning the protection of professional education for specialist Doctor participants from psychological violence and bullying, while proposing an ideal regulatory reformulation to safeguard their rights. Employing normative legal research methods with legislative, doctrinal, and responsive legal theory approaches, the study reveals that existing regulations such as Law Number. 20 of 2013 on Medical Education fail to provide explicit protections for professional education for specialist Doctor participants. Meanwhile, the Minister of Health’s Instructions remain merely administrative and lack legally binding force. Regulatory reform should clearly define professional education for specialist Doctor participants’ status within the national education system, specify the rights and obligations of program organizers and participants, establish an independent anti-bullying task force, and implement monitoring mechanisms and administrative sanctions. A victim-oriented, responsive regulatory framework would not only protect trainees’ rights but also enhance the quality of medical education and national healthcare services. The state must act promptly through progressive legislation to eradicate bullying practices and ensure a fair, humane educational environment for professional education for specialist Doctor participants.